Analysis of Dual-Reflector Antenna for Radar Applications - Imani, A.; Soleimani, M.; Amiri, S. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A dual-reflector antenna in millimeter wave frequency band is designed at center frequency of 35 GHz. The designed antenna has small size, low weight, fast beam scanning, high efficiency and high gain. Beam rotation of the proposed structure makes it useful for wide angle scanning in modern airborne radar systems. In the literature, beam rotation of similar structures used to be evaluated by two times of the twist-reflector rotation. For the first time, a nonlinear relationship is found between beam rotation and twist-reflector rotation. This nonlinear relation is theoretically extracted in this work. Furthermore, the designed antenna is simulated with a commercial full wave package. The results confirm that the designed goals are addressed. Moreover, the simulation results validate the extracted analytic relationship between beam rotation and twistreflector rotation. In addition, low VSWR, low crosspolarization and good radiation pattern are observed.